Therapeutic Exercise and Conservative Injection Treatment for Early Knee Osteoarthritis in Athletes: A Scoping Review - Lucrezia Tognolo; Maria Chiara Maccarone; Stefania De Trane; Anna Scanu; Stefano Masiero; Pietro Fiore (Medicina, 2022)
Background and Objectives: Recent evidence highlighted a higher prevalence of knee osteoarthritis (kOA) among young and former ex-professional athletes. Although the practice of a highly demanding sport is considered a predisposing factor for the knee joint cartilage degeneration, articular cartilage seems to positively respond to a moderate load increase. We aim to investigate recent evidence on the conservative management of early kOA in athletes, with a particular emphasis on therapeutic exercise and injection treatment, in order to highlight whether there are any indications that can influence clinical and rehabilitation practice. Materials and Methods: A scoping review was conducted, screening MEDLINE and PEDro databases for studies published over the past twenty years on the topic. Studies in English, with accessible abstracts, were included in the review. The PICO framework was used (P—patient: athletes, I—Intervention: conservative treatment with therapeutic exercise or injection therapies, C—Comparison: not needed, O—Outcomes: clinical outcomes). Clinical trials, randomized controlled trials, and longitudinal studies were considered. Results: Four studies were finally included in the review. Therapeutic exercise seems to have beneficial effects on prevention of cartilage degeneration, on pain reduction, and on physical function enhancement. On the other hand, in mild to moderate stages of kOA the intra-articular viscosupplementation with Hyaluronic Acid showed a medium to long-term improvement in joint pain and function. The Platelet Rich Plasma treatment also showed a significant improvement in pain and function up to 12 months. Conclusions: Despite the heterogeneity of the studies considered, a multimodal treatment combining therapeutic exercise and moderate aerobic activity (such as running) should be indicated to prevent kOA development. In cases of symptomatic kOA it may be indicated to add minimally invasive injection therapy that seems to contribute to the improvement of motor function and symptomatology.